3‐O‐Laurylglyceryl ascorbate improves the development of sensitive skin through the reduction of oxidative stress. (30th January 2019) - Katsuyama, Yushi; Taira, Norihisa; Tsuboi, Tatsuya; Yoshioka, Masato; Okano, Yuri; Masaki, Hitoshi
Abstract: Skin sensitivity is a serious problem for many people, and it can be induced by various factors such as UV irradiation, physical and mental stresses, air pollution, dry air and so on. Skin dryness triggered by UV and dry air is one of the most important causes inducing the development of sensitive skin, and it has been reported that oxidative stress contributes to skin dryness. In this study, we investigated whether treatment with 3‐ O ‐laurylglyceryl ascorbate (VC‐3LG), which is an amphipathic ascorbic acid derivative, can suppress the development of sensitive skin. The results demonstrate that VC‐3LG restores the expression levels of interleukin‐1α, nerve growth factor and matrix metalloprotease‐9 in the dry skin models of reconstructed human epidermal equivalents (RHEEs) and in H2 O2 ‐treated keratinocytes. In addition, VC‐3LG suppresses the dendrite elongation of nerve cells induced in RHEEs by dry skin conditions and by H2 O2 treatment of keratinocytes. Therefore, we consider that treatment of the skin with VC‐3LG is an effective approach to improve the development of sensitive skin.